2022
DOI: 10.1177/10892532221100663
|View full text |Cite
|
Sign up to set email alerts
|

Year in Review 2021: Noteworthy Literature in Cardiothoracic Critical Care

Abstract: This year marked a number of milestones in critical care. As vaccines for the SARS-CoV-2 virus became widely available and were confirmed to be exceptionally effective against severe illness and hospitalization, we were then faced with new variants and the resource-intense responses necessary to combat them. Despite challenges new and old, we have persevered and continued to provide excellent care to our patients while pushing the boundaries of clinical research. This article is a collection of studies publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 38 publications
4
8
0
Order By: Relevance
“…A recent study evaluating the administration the use of dexamethasone did show a reduction in post-operative delirium, but it was unable to demonstrate statistical significance. 5 An additional study demonstrated a reduction in the amount of time on mechanical ventilation in addition to time in the ICU, and these results correlate with prior studies. 5 Predicting patients at risk for post-operative AKI after cardiac surgery is an ongoing topic of discussion, given that post-op AKI itself is a risk factor for increased mortality.…”
Section: Cardiothoracic Icusupporting
confidence: 80%
See 4 more Smart Citations
“…A recent study evaluating the administration the use of dexamethasone did show a reduction in post-operative delirium, but it was unable to demonstrate statistical significance. 5 An additional study demonstrated a reduction in the amount of time on mechanical ventilation in addition to time in the ICU, and these results correlate with prior studies. 5 Predicting patients at risk for post-operative AKI after cardiac surgery is an ongoing topic of discussion, given that post-op AKI itself is a risk factor for increased mortality.…”
Section: Cardiothoracic Icusupporting
confidence: 80%
“…5 An additional study demonstrated a reduction in the amount of time on mechanical ventilation in addition to time in the ICU, and these results correlate with prior studies. 5 Predicting patients at risk for post-operative AKI after cardiac surgery is an ongoing topic of discussion, given that post-op AKI itself is a risk factor for increased mortality. The authors discuss a feasibility study evaluating a noninvasive device which measures urine oxygen partial pressure (predictive of post-operative AKI in cardiac surgery patients) to determine its ability to predict patients who may go on to develop AKI based on urine oxygen partial pressure cutoffs following CPB.…”
Section: Cardiothoracic Icusupporting
confidence: 80%
See 3 more Smart Citations